Further Insights into Developmental Brain Malformations and Leukoencephalopathy Associated with 6p25.3 Deletion - Eid, Maha; Eid, Ola; Hegazy, Ibrahim; Girgis, Marian; Mohamed, Amal; Abdel-Salam, Ghada M.H. (Neuropediatrics, 2020)
We report a new patient who presented with dysmorphic features and congenital heart disease. In addition, her brain magnetic resonance imaging revealed leukoencephalopathy, cavum septum pellucidum, perisylvian polymicrogyria, and focal occipital pachygyria. Her regular karyotype showed 46,XX add 6 (p25) due to malsegregation of a maternal balanced translocation 46,XX,t(6;7)(p25;q33) while the array-comparative genomic hybridization identified a 3.307 Mb heterozygous deletion at 6p25.3-p25.2 and 23.95 Mb duplication at 7q33-q36.3. A previous patient with the same developmental brain malformations and leukoencephalopathy with 6p25 deletion including TUBB2A and TUBB2B genes had been reported. Thus, confirming that these specific developmental brain malformations are due to TUBB2A and TUBB2B haploinsufficiency. Our report is the first to present the developmental brain malformations associated with whole gene deletions of the two tubulin genes and provide further insights into the etiology of developmental brain malformations and white matter abnormalities associated with 6p25 deletions.
Keywords: 6p25 deletion; 7q33-q36.3 duplication; leukoencephalopathy; pachygyria; polymicrogyria; atrial septal defect; TUBB2A; TUBB2B